Contribution of Academic Science to the Development of a University: to the 100th Anniversary of the Kuban State Medical University - S. N. Alekseenko; A. N. Red’ko; I. L. Cherednik; D. V. Veselova; T. A. Kovelina; E. L. Nikulina (Кубанский научный медицинский вестник, 2020)
The academic potential of the Kuban State Medical University has been formed as a result of close interaction between university and academic science. Such collaboration encourages the development of highly qualifi ed academic and teaching staff, increases the importance of conducting fundamental studies and forms an information basis for boosting research and educational processes in the university. Over a century, academicians and corresponding members of the Russian Academy of Sciences (RAS) have contributed to the development of the Kuban State Medical University by taking part in fundamental research projects and creating scientifi c schools. The Kuban State Medical University has received ongoing intellectual support from representatives of academic science both in the formation of long-term developmental strategies and implementation of individual scientifi c projects. The collaboration between RAS and the university has been carried out under different socio-economic and political conditions. The Kuban State Medical University will continue implementation of fundamental research projects in close interaction with the Russian Academy of Sciences (RAS) in the foreseeable future. This article presents a brief biography of 15 RAS academicians and corresponding members having made a signifi cant contribution to the development of the Kuban State Medical University, which is celebrating its 100th anniversary this year.